Legal Aspect Marriage in Under Age Child - Christian Daniel Hermes; Rosita Nainggolan (Budapest International Research and Critics University, 2022)
This study aims to determine how the occurrence of underage marriage and how the effects of underage marriage. Marriage is an inner and outer bond which binds themselves to become husband and wife. This study discusses the many impacts that occur due to underage marriage even though the Marriage Law has changed. Law of the Republic of Indonesia No. 16 of 2019 concerning Amendments to Law No. 1 of 1974 concerning Marriage, says